(untitled) (Bangladesh Journal of Animal Science, 2016)
An experiment was conducted to determine the effect of organic acids (acetic, butyric, citric and formic acids) on growth and nutrient digestibility of broilers. One hundred fifty (150) day old Hubbard chicks were used. There were five dietary treatments such viz Diet 1 as control contained no organic acid, diets 2, 3, 4, and 5 contained 0.25% acetic, butyric, citric and formic acids, respectively. Each treatment was replicated three times having 10 birds arranged in completely randomized design (CRD). Feed and water were given ad libitum. Feeding of organic acid diets lasted for 7 weeks starting from the second week. At the starter phase, formic acid improved live weight. Feed and water intakes were significantly (P<0.05) reduced by butyric acid. Feed: gain ratio was improved by formic acid. At the finisher phase, live weight was significantly (P<0.05) improved by the acids except butyric acid. Feed intake, daily gain and feed: gain ratio were not significant (P>0.05). Crude protein and ether extracts digestibility were improved by all the organic acids (P<0.05). It is therefore concluded that 0.25% formic acid could be added to broiler diets. Bang. J. Anim. Sci. 2016. 45 (2): 10-17